Deconstruction of Local Culture: Misbah Musthofa's Critique in Tafsir Al-Iklīl Fī Ma'āni Al-Tanzīl on the Traditions of Javanese Islamic Societies - Ahmad, Nehru Millat; Anam, Saichul; Wan Mokhtar, Wan Khairul Aiman; Gunawan, Muhammad Ali (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
The interaction between Islam and Javanese culture has not only produced a dynamic dialectic but has also often generated tension when local traditions intersect with the normative values of the Qur’an. This study aims to analyze the relationship between the Qur’an and local culture through the deconstruction of Javanese religious traditions as represented in Tafsir Al-Iklīl fī Ma‘ānī al-Tanzīl by Misbah Musthofa. Employing a qualitative method with a sociological approach to Qur’anic exegesis, this study examines how interpretation is shaped through the interrelation between the exegete and the socio-cultural context of his community. The primary data are drawn from the text of Tafsir Al-Iklīl fī Ma‘ānī al-Tanzīl, while supporting data are obtained from relevant secondary literature. The findings reveal that Tafsir Al-Iklīl represents a contextual model of Qur’anic interpretation grounded in the social reality of Javanese Muslim society. Through his critique of traditions such as tahlilan, excessive grave visitation, teacher veneration, ruwatan, and tumpengan, Misbah Musthofa emphasizes the Qur’an’s role as both a means of purifying faith and a vehicle for cultural transformation. His interpretive structure displays a deconstructive pattern in which the Qur’anic text is not merely explained literally but projected as a form of social critique against religious practices influenced by pre-Islamic elements. Misbah Musthofa establishes a hermeneutical relationship between the divine text and cultural context, producing a progressive and emancipatory model of exegesis. Although rooted in the pesantren (Islamic boarding school) tradition, his interpretation demonstrates a strong rational and moral orientation, positioning the Qur’an as a “living text” that continuously dialogues with contemporary realities. These findings indicate that the deconstruction of local culture in Tafsir Al-Iklīl constitutes a reformulation of Javanese pesantren exegesis toward a critical, reflective, and transformative socio-cultural mode of interpretation.